Mechanisms of pathogenesis and molecular targets in spinal and bulbar muscular atrophy - Rinaldi, Carlo (Henry Stewart Talks, 2016)
Etiology and molecular pathogenesis, Histopathological and clinical features, Differential diagnosis, Experimental therapies